Crime and Establishment Size: Evidence from South America - Umut Oguzoglu; Ashantha Ranasinghe (Institute for the Study of Labor (IZA), 2015)
Establishment exposure to crime is a frequent occurrence and a major obstacle to business operation in developing economies. We present a simple theory for the frequency and severity of crime across establishment size that is validated against the data in South America. We find that high expectation of crime at the establishment- level is strongly associated with lower sales, labor and capital investment, and consistent with our theory is most evident among medium size establishments. We consider a variety of specifications that are tenable with a causal interpretation of our results. Moreover, when evaluated relative to a host of distortions emphasized in the literature, crime remains important for explaining establishment size and addressing it may be one of the more important policy reforms for spurring development in South America.
Keywords: O1; O4; D2; 330; crime; establishment size; misallocation